Scurvy with Musculoskeletal Pain in Indonesian Pediatric Patient: A Case Report - Hilmi Muhammad; Meirizal Meirizal; Yudha Mathan Sakti; Aditya Fuad Robby Triangga; Zikrina Abiyanti Lanodiyu; Ginanjar Reza Putra; Yasser Yasser; Yuni Artha Prabowo Putro (Jurnal Kedokteran Diponegoro (Diponegoro Medical Journal), 2024)
Background: Scurvy is a potentially fatal disease caused by a severe deficiency of vitamin C, which can manifest as a musculoskeletal problem. Early diagnosis and treatment of vitamin C deficiency are crucial to prevent severe symptoms. Unfortunately, vitamin C level evaluations in Indonesia are very limited due to the lack of laboratory facilities. As a result, patients with scurvy are often underdiagnosed and do not receive adequate management. Case Presentation: 5-year-old boy with musculoskeletal pain and inability to walk. Radiographic findings showed a pathognomonic line of Fränkel, Trümmerfeld zone, and Wimberger ring sign, with laboratory evaluation showing an anemia and vitamin D deficiency. We did not perform a laboratory examination for vitamin C due to a lack of test facilities but the patient was given oral 250 mg of vitamin C daily instead. The patient showed significant improvement in symptoms and laboratory results after three months of vitamin C supplementation. To summarize, that vitamin C deficiency should be considered among patients with related musculoskeletal manifestations supported by imaging results.